Remote ischaemic preconditioning does not modulate the systemic inflammatory response or renal tubular stress biomarkers after endotoxaemia in healthy human volunteers: a single-centre, mechanistic, randomised controlled trial. (August 2019) - Zwaag, J.; Beunders, R.; Warlé, M.C.; Kellum, J.A.; Riksen, N.P.; Pickkers, P.; Kox, M.
Abstract: Background: Remote ischaemic preconditioning (RIPC) consists of repeated cycles of limb ischaemia and reperfusion, which may reduce perioperative myocardial ischaemic damage and kidney injury. We hypothesised that RIPC may be beneficial by attenuating the systemic inflammatory response. We investigated whether RIPC affects the response in humans to bacterial endotoxin (lipopolysaccharide [LPS]) by measuring plasma cytokines and renal cell-cycle arrest mediators, which reflect renal tubular stress. Methods: Healthy male volunteers were randomised to receive either daily RIPC for 6 consecutive days (RIPCmultiple, n =10) plus RIPC during the 40 min preceding i.v. LPS (2 ng kg −1 ), RIPC only during the 40 min before LPS (RIPCsingle, n =10), or no RIPC preceding LPS (control, n =10). As a surrogate marker of renal tubular stress, the product of urinary concentrations of two cell-cycle arrest markers was calculated (tissue inhibitor of metalloproteinases-2 [TIMP2]*insulin-like growth factor binding protein-7 [IGFBP7]). Data are presented as median (inter-quartile range). Results: In both RIPC groups, RIPC alone increased [TIMP2]*[IGFBP7]. LPS administration resulted in fever, flu-like symptoms, and haemodynamic alterations. Plasma cytokine concentrations increased profoundly during endotoxaemia (control group: tumor necrosis factor alpha [TNF-α] from 14 [9–16] pg ml −1 at baseline to 480 [284–709] pg ml −1 at 1.5 h after LPS; interleukin-6 [IL-6] from 4 [4–4] pg ml −1 at baseline to 659 [505–1018] pg ml −1 at 2 h after LPS). LPS administration also increased urinary [TIMP2[*[IGFBP7]. RIPC had no effect on LPS-induced cytokine release or [TIMP2]*[IGFBP7]. Conclusions: RIPC neither modulated systemic cytokine release nor attenuated inflammation-induced tubular stress after LPS. However, RIPC alone induced renal markers of cell-cycle arrest. Clinical trial registration: NCT 02602977.